Recycling silicon from silicon cutting waste by Al–Si alloying. (1st April 2020) - Wei, Donghui; Gao, Shuaibo; Kong, Jian; Jin, Xing; Jiang, Shengnan; Zhou, Shibo; Zhuang, Yanxin; Yin, Huayi; Xing, Pengfei
Abstract: Large amounts of silicon cutting waste (SCW) will be generated as the photovoltaic (PV) industry grows, which not only wastes valuable resources, but also causes environmental issues if SCW is not addressed. In this study, a novel and effective method to recycle Si from SCW by Al–Si alloying with a cryolite additive is proposed. The influence of the smelting parameters including smelting temperature, holding time and cryolite/SCW ratio, on the Si content of alloys and the utilization ratio of SCW was investigated and optimized. The optimal conditions were a smelting temperature of 1150 °C, holding time of 30 min and cryolite/SCW ratio of 6.3. Under these optimized conditions, the Si content of alloys and the utilization ratio of SCW were 12.02 wt% and 64.25%, respectively. The characterization analysis results of the products showed that Al–Si alloys with a uniform distribution of Si were successfully prepared. Furthermore, the mechanism of the alloying process was studied. Cryolite additives can efficiently dissolve the SiO2 film on the surface of Si particles and hence contribute to the subsequent transfer of the exposed Si to molten Al. The study of the slag-metal interface demonstrates that Si is recycled with a highly efficiency from SCW. Despite the relatively large amount of cryolite, the generated slag can be recycled and used as an additive for the next batch of experiments. This method not only recycles silicon scrap for use as valuable raw materials, but also reduces the production cost of Al–Si alloys, and thus, this method is a feasible way to commercially recycle SCW in an economically and environmentally friendly manner. Graphical abstract: Image 103 Highlights: Recycling of silicon cutting waste (SCW) was achieved by a new Al–Si alloying process. Cryolite was applied to improve the recycling effect of Si from SCW. The Si in SCW was recycled at a relative lower temperature about 1000–1200 °C. The recycling process is simply, effectively and easily to be industrialized.